The Impact of Character Education Policy on the Moral Formation of Children in West Java - Naima Ima (Mauve Journal De Leardu, 2024)
This observe investigates the impact of man or woman education rules on the ethical and socio-emotional improvement of kids in West Java, Indonesia. Through a complete analysis encompassing descriptive statistics, paired-samples t-assessments, regression analyses, ANCOVA, and Pearson correlational analyses, the examine explores the efficacy of character education programs in enhancing empathy stages, ethical reasoning abilties, and prosocial behaviors amongst contributors. The findings display vast enhancements in empathy scores following participation in man or woman schooling projects, with both person education publicity and parental involvement identified as key predictors of ethical reasoning abilities. The look at additionally highlights the nice correlations between person schooling publicity, parental involvement, and empathy ratings, underscoring the interconnectedness of these elements in promoting moral values and social-emotional nicely-being among youngsters. These insights contribute to the discourse on man or woman training and tell techniques for fostering holistic development and responsible citizenship.